2017
DOI: 10.1152/physrev.00040.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neoteny, Prolongation of Youth: From Naked Mole Rats to “Naked Apes” (Humans)

Abstract: It has been suggested that highly social mammals, such as naked mole rats and humans, are long-lived due to neoteny (the prolongation of youth). In both species, aging cannot operate as a mechanism facilitating natural selection because the pressure of this selection is strongly reduced due to ) a specific social structure where only the "queen" and her "husband(s)" are involved in reproduction (naked mole rats) or) substituting fast technological progress for slow biological evolution (humans). Lists of numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 152 publications
5
86
0
6
Order By: Relevance
“…NMRs are eusocial animals that live in colonies where only a subgroup of animals is devoted to reproduction (usually a queen and one male called pasha) [2]. NMRs exhibit other exceptional traits including lifelong fertility, resistance to infection, high regenerative capacity, resistance to cancer and diabetes, reviewed in [3,4]. For these reasons, NMRs have drawn attention of multiple studies aimed at identifying the molecular mechanisms behind their extreme longevity and resistance to age-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…NMRs are eusocial animals that live in colonies where only a subgroup of animals is devoted to reproduction (usually a queen and one male called pasha) [2]. NMRs exhibit other exceptional traits including lifelong fertility, resistance to infection, high regenerative capacity, resistance to cancer and diabetes, reviewed in [3,4]. For these reasons, NMRs have drawn attention of multiple studies aimed at identifying the molecular mechanisms behind their extreme longevity and resistance to age-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these features, such as splenic hematopoiesis, are characteristic of embryonic stage in other mammals. It had been proposed that long-lived naked mole rats, as well as humans, display neotenic traits compared to their shortlived relatives (Skulachev et al, 2017). Furthermore, many characteristics of the naked mole rat hematopoietic system showed higher similarity to humans than to mice ( Figure S7D).…”
Section: Discussionmentioning
confidence: 97%
“…A common hallmark of hematopoietic lineage trajectories is a differentiation bias of HSCs along the MK lineage (Sanjuan-Pla et al, 2013). However, this bias is shifted in naked mole-rats towards HSC/MEP transition, resembling the fetal HSC bias towards the entire red lineage, therewith constituting a further neotenic trait of naked mole-rats (Skulachev et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Neoteny is an example of the more general phenomenon of heterochrony in which different systems or parts of an organism develop at different rates with respect to an ancestor, some accelerated and others, such as neoteny, retarded. Some neotenous human characteristics include infant‐like facial features in adults (e.g., rounded head, nonprotruding jaw), late eruption of teeth, orientation of the pelvis, and retention of prenatal brain growth rates after birth, among others (see Gould, ; Skulachev et al., ; Somel et al., ). For example, researchers using microarrays and RNA sequencing reported that peak expression of genes associated with synaptic function is delayed to 5 years in humans, compared to < 1 year in macaques and chimpanzees, and hypothesized that this change may have occurred after Homo sapiens split from the Neanderthal lineages (Liu et al., ; see also Somel et al., ).…”
Section: Embryos and Ancestorsmentioning
confidence: 99%